"We are not the language police": Comparing multilingual EMI programmes in Europe and Asia. (18th December 2018) - Baker, Will; Hüttner, Julia
Abstract : English medium instruction (EMI) in higher education has rapidly increased over the last decade in Europe and Asia. However, this expansion has far outstripped research and many key questions remain unanswered. This study addresses a number of those questions related to roles and conceptualisations of English and other languages in multilingual university settings. Data is presented from an exploratory mixed‐methods (121 questionnaire responses and 12 interviews with lecturers and students), comparative study of higher education institutes in the UK, Austria and Thailand. Findings showed a move from monolingual orientations at management level, mixed responses to multilingualism in ideologies and beliefs, to extensive multilingualism and complexity in practices. Furthermore, unexpected similarities between the UK and Thailand as regards language proficiency and content learning were found.